Personalised cardiovascular disease risk information as a motivator of behaviour change in individuals at high cardiovascular disease risk - Price, H; Hermione Price (2010)
Introduction: Cardiovascular disease (CVD) risk assessment is becoming increasingly common in routine clinical practice. Consequently many individuals are likely to be identified as being at increased CVD risk and risk reducing strategies implemented with a view to preventing future CVD. There are many steps along the pathway from CVD risk assessment to the prevention of CVD events. First, CVD risk needs to be accurately estimated using an appropriate CVD risk calculator. Secondly CVD risk information needs to be effectively communicated to the individual identified as being at increased risk. Thirdly, the risk information communicated needs to be capable of motivating behaviour change and finally behaviour change needs to result in a reduction in CVD risk. The evidence base for many of these steps has yet to be fully established. Aims: The overall aims of this work were first to adapt the United Kingdom Prospective Diabetes Study (UKPDS) Risk Engine to better display risk and achievable risk. Secondly to investigate lay perceptions of risk and to develop two interventions designed to reduce CVD risk. The two interventions were a personalised 10-year CVD risk estimate and a brief lifestyle advice intervention. Finally, the capacity of these interventions to increase physical activity and improve CVD risk factors in adults at increased CVD risk was tested. Methods: Three focus groups were held to investigate lay perceptions of risk and to inform the design of the UKPDS Risk Engine interface and a brief lifestyle advice intervention designed to motivate risk reducing behaviours. The two interventions were then tested in a 2x2 factorial randomised controlled trial. Results: The focus group results demonstrated that public interest and understanding of risk was high. In addition participants expressed clear views regarding how risk information and lifestyle advice should be presented. 194 participants at increased 10-year CVD risk (≥ 20%) were recruited from 4 Oxfordshire general practices. Neither a personalised 10-year CVD risk estimate nor a brief lifestyle advice intervention was capable of increasing physical activity or reducing estimated 10-year CVD risk in this group. Conclusions: Whilst public interest in CVD risk appeared to be high this study was unable to demonstrate that a 10-year personalised CVD risk estimate or a brief lifestyle advice intervention was able to increase physical activity in adults at increased CVD risk.